Integrating Pancasila Values Through the Game Of Pecah Piring: A Reflective Study at Al-Azhar - Rahmi Rahmadani; Marzuki; Aldy Saputra; Ricad Michael Sihombing (Jurnal Kewarganegaraan, 2026)
This study aims to explore the integration of Pancasila values through the traditional game Pecah Piring as a reflective pedagogical approach in Civic Education at the junior high school level. The background of this study stems from the weak practice of Pancasila values among students, as well as the dominance of cognitive and theoretical learning in Civic Education. The research used a qualitative approach with a reflective study design. Data were collected through learning observations, student reflection journals, and teacher field notes, then analysed using reflective thematic analysis techniques. The results of the study show that the Pecah Piring game not only creates a fun and participatory learning experience, but also facilitates the process of internalising Pancasila values. Student reflections show a shift from mere involvement in play to an awareness of values, such as honesty and religiosity, discipline and justice, solidarity and cooperation, deliberation and democracy, as well as responsibility and sportsmanship. These findings confirm that traditional games can function as an effective experience-based learning medium in connecting local wisdom with civic education. The novelty of this research lies in the interpretation of traditional games as a reflective pedagogical strategy to strengthen the internalisation of Pancasila values in learning.